Clinical impact of early post-transplant red cell transfusions in kidney transplantation: a systematic review and meta-analysis - Hassan, Sevda; Gleeson, Sarah; Thomson, Tina; Spensley, Katrina J.; Dor, Frank; Brown, Colin; Regan, Fiona; Pengel, Liset H. M.; Willicombe, Michelle; Roberts, David J. (Frontiers in Transplantation, 2023)
Red blood cell transfusions (RBCT) represent a potentially modifiable risk factor for HLA sensitisation and adverse outcomes post transplantation. Evidence of the clinical impact of post-transplant RBCT has been infrequently reported. Here, we performed a systematic review of available literature to assess the prevalence of RBCT post kidney transplant, and the effect of transfusion on transplant outcomes.We included studies from 2000 to July 2022, published on Medline, Embase and the Transplant Library.Ten studies were analysed which included a total of 32,817 kidney transplant recipients, with a median transfusion prevalence of 40% (range 18-64%). There was significant heterogeneity between studies in terms of patient and allograft characteristics, immunological risk, and immunosuppression protocols.Analysis of unadjusted outcomes showed that post-transplant RBCTs are associated with inferior patient survival, allograft loss, rejection and donor specific antibodies. Adjusted outcomes were described where available, and supported the adverse associations seen in the unadjusted models in many studies. Despite limitations, this review demonstrates that RBCT post-transplant are common, and maybe associated with inferior outcomes, but highlights the urgent need for high quality prospective evidence of the independent effect of RBCTs on transplant outcomes.